If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4d = -6 + -9d Solving 6 + -4d = -6 + -9d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '9d' to each side of the equation. 6 + -4d + 9d = -6 + -9d + 9d Combine like terms: -4d + 9d = 5d 6 + 5d = -6 + -9d + 9d Combine like terms: -9d + 9d = 0 6 + 5d = -6 + 0 6 + 5d = -6 Add '-6' to each side of the equation. 6 + -6 + 5d = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 5d = -6 + -6 5d = -6 + -6 Combine like terms: -6 + -6 = -12 5d = -12 Divide each side by '5'. d = -2.4 Simplifying d = -2.4
| 4(5x-3)=10x+8 | | 9m-7-4m= | | 9x^2+24x-22=0 | | 3+2n=-3 | | y=x^2+kx+100 | | 5x+3=3(x-3) | | 5x+42=2x+18 | | 32+2x=8x-16 | | 7x-68=9x-96 | | -12.19-0.5x=5.3(x+3.5) | | 7(3x+2)=3(x+2)-17 | | ln(x+3)-4=ln(x-5) | | 5+2(3y-1)=2y-5 | | 100x-4x^2=20 | | 4x^2-25x+14=-4x+9 | | 4v-24=8v | | 7(c+2.1)=14c-0.7 | | 56(7)= | | 1.5(y-10)=0.4-y | | 3x+21=48+2x | | -8=x-2y | | 14=p-8 | | 1/4t+1/3t=7/12 | | 0.05+0.01x=6x | | 2(x+3)=6x-12 | | 5(2x+3x)-20=55 | | 100-4x=20 | | 6x+3y=16 | | 100-4x= | | t^2=33 | | 3x+9=21x | | x+(x-6)+15=39 |